A HOLISTIC APPROACH OF TRANSPERSONAL COUNSELING IN EDUCATIONAL SETTINGS TO IMPROVE ADOLESCENTS’ PSYCHOLOGICAL WELL-BEING - Wayan Eka Paramartha; I Ketut Dharsana (EDUCATIONE, 2025)
Psychological well-being enables adolescents to feel happy, have a sense of purpose, and manage emotional and social pressures effectively. However, many adolescents face stress due to academic demands, social expectations, and emotional disturbances, disrupting their psychological balance. Existing interventions often lack a holistic approach and fail to effectively integrate psychological, emotional, and spiritual aspects to enhance psychological well-being. This study aims to evaluate the effectiveness of transpersonal counseling as an intervention to improve adolescents' psychological well-being. The method employed was a quasi-experimental design with pre-test and post-test, involving 20 adolescents aged 15-18 years selected through purposive sampling. The results indicated that the average psychological well-being score significantly increased from 62.5 in the pre-test (low category) to 81.7 in the post-test (higher category). Statistical analysis using a related sample t-test yielded a t-value of 5.32 with a p-value < 0.05, signifying a significant difference before and after the intervention. These findings suggest that transpersonal counseling can be an effective approach to improving adolescents' psychological well-being through a holistic integration of psychological, emotional, and spiritual dimensions.